O controle de preensão em pinça em adultos jovens: efeito da posição do punho - Andrade, Vanessa Luzia Barros de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The human hand is the focus of inumerous research studies. Human individuals are capable of performing manual tasks beyond the ability of any other animal. Such large motor ability is due in part to contact surface of the pulp thumb in opposition to the other fingers. Evidences in the literature show that the position of the upper limb influences the ability of hand strength and control. Specifically, the position of the wrist has great influence on the production of pinch strength. The main objective of this study was to investigate the influence of wrist position on the pinch grip with the thumb in opposition to the index finger. Participants of the present study were 21 undergraduate students, 10 men and 11 women. Participants performed a pinch grip task in three wrist positions - maximum flexion, maximum extension and neutral - on two force conditions - 20% and 40% of maximum voluntary contraction (MVC). MVC was measured in two attempts in each of the three positions of the wrist for a period of three seconds, and the trial of the best result was used as the parameter for task performance. In each trial participants maintained the force production at position for 10 seconds. All participants performed each test condition four times, and the first was used as a familiarization trial and discarded from further analysis. In all trials visual feedback online was provided. Results of both group gender showed variability was similar for force production. Men were stronger than women, but this difference was not significant and both produced on the average more strength in the neutral wrist position than in flexion or extension. In the extended position participants were significantly less variable than in the flexion and neutral positions. We obtained a significant positive correlation between weight and pinch force...(Complete abstracts click electronic access below)

A mão humana tem sido foco de estudo de muitos cientistas devido à sua funcionalidade e peculiar mobilidade. O homem é capaz de executar tarefas manuais muito além das possíveis a qualquer outro animal. Esta vasta capacidade motora se deve ao íntimo contato da superfície polpuda do polegar em oposição à dos demais dedos. Evidências na literatura mostram que a posição do membro superior influencia na capacidade de produção de força da mão. Especificamente, a posição do punho tem grande influência sobre a produção de força em pinça. O objetivo principal deste estudo foi investigar a influência da posição do punho na preensão em pinça com o polegar em oposição ao dedo indicador. Participaram do estudo 21 universitários dos quais 10 eram homens e 11 mulheres. Os participantes realizaram uma tarefa de preensão em pinça em três posições do punho: flexão máxima, extensão máxima e neutra em duas condições de força – 20% e 40% da contração voluntária máxima (CVM). A CVM foi mensurada, por um período de três segundos, em duas tentativas de produção de força em cada das três posições do punho e a tentativa de melhor resultado foi usada como parâmetro para a realização das tarefas. Em cada uma das condições de posição do punho, os participantes mantiveram a produção de força, por um período de 10 segundos. Todos os participantes executaram cada condição da tarefa quatro vezes, sendo que a primeira foi utilizada para familiarização com a tarefa e descartada das análises. Em todas as tentativas foi fornecido feedback visual em tempo real. Os resultados mostram que homens e mulheres apresentam variabilidade semelhante de produção de força. Os homens são consistentemente mais fortes que as mulheres e ambos produzem, em média, mais força...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ergonomia; Mãos; Realimentação (Psicologia); Força; Strength